Predictors of major adverse cardiovascular events in patients with heart failure with reduced ejection fraction. (2nd May 2022) - Tinoco, M; Cardoso, F; Dias, G; Pereira, T; Faria, B; Almeida, F; Leite, S; Lourenco, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Heart failure (HF) is a growing epidemic, currently affecting more than 26 million people around the globe. Outcomes of patients with HF with reduced ejection fraction (HFrEF) are generally poor. Thus, it is important to recognize outcome predictors in order to better identify and manage patients at higher risk. Purpose: The aim of this study was to identify predictors of major adverse cardiovascular events (MACE) in patients with HFrEF. Methods: Retrospective study of patients with HFrEF observed at an HF clinic between Jan 2018 and Dec 2018, with a follow up at Sept 2021. We define MACE as composite of death from cardiovascular (CV) causes or hospitalization for HF. Clinical characteristics and MACE were analysed during the follow-up. Cox analysis was used to identify predictors of MACE. Results: A total of 138 patients were included: 82, 6% (114) male, 61, 4±11, 3 years. The most frequent underlying aetiologies for HF were ischemic cardiomyopathy (44, 9%; 62) and dilated cardiomyopathy (47, 8%, 66). Mean left ventricular ejection fraction (LVEF) was 26±9% and right ventricular dysfunction was present in 27% of the cases. A total of 62, 3% (86) of patients were medicated with angiotensin converting enzyme inhibitors (ACEI)/angiotensin receptor blocker (ARB), 32, 6% (45) with sacubitril-valsartan, 92% (127) with beta-blockers (BB), 84, 8% (117) with mineralocorticoid receptor antagonists (MRA) and 34, 1% (47) with sodium-glucose co-transporter-2 inhibitors (iSGLT2). A total of 36, 2% (50) of patients had an ICD and 34, 1% (47) had a CRT-D. During a median follow-up of 40 months (IQR: 32-58), MACE occurred in 35, 5% (49) of patients of which 10, 1% (14) died for CV causes and 25, 4% (35) had hospitalizations for HF. The median time to MACE was 29 months (IQR: 12-46). A total of 12, 3% (17) of patients died for non-CV causes. Sixty percent of patients (21) previously hospitalized for HF were rehospitalised for HF during the follow-up. Factors such as NYHA functional class at the beginning of follow-up (log rank=0, 001), admission elevated levels of PBNP (> 500ng/L) (log rank=0, 016), absence of iSLT2 therapy (log rank=0, 011), absence of BB therapy (log rank=0, 017), furosemide therapy (log rank <0, 001), metolazone therapy (log rank=0, 033), need of inotropic support (log rank<0, 001), emergency department visits for acute HF (log rank <0, 001), HF hospitalizations (log rank <0, 001) and absence of LVEF recovery (log rank=0, 015) were associated with a higher risk of MACE during the follow up. In the multivariate analysis, only absence of iSGLT2 therapy (p= 0, 009) and the need of inotropic support (P< 0, 001) were significantly associated with the risk of MACE. Conclusion: Patients with HFrEF had a poor outcome with one third of patients having MACE and 10% of patients dying for CV causes during the follow-up. In this polymedicated ambulatory population, the therapy with iSGLT2 seems to bring an additional benefit in MACE reduction.